Orlistat Therapy for Children With Type 1 Hyperlipoproteinemia: A Randomized Clinical Trial - Patni, Nivedita (J Clin Endocrinol Metab, 2018)
CONTEXT: Patients with type 1 hyperlipoproteinemia (T1HLP), a rare genetic disorder, have extreme chylomicronemia and recurrent episodes of acute pancreatitis. Currently, the only therapeutic option is to consume an extremely low-fat diet because the triglyceride-lowering medications are not efficacious. OBJECTIVE: To determine the efficacy of orlistat, a gastric and pancreatic lipase inhibitor, in reducing serum triglyceride levels in patients with T1HLP. DESIGN AND SETTING: We conducted a randomized, open-label, clinical trial with a four-period, two-sequence (“orlistat” and “off orlistat” for 3 months), crossover study design. PATIENTS: Two unrelated young Asian Indian males (11 and 9 years old) with T1HLP due to homozygous large GPIHBP1 deletions were enrolled at the UT Southwestern Medical Center. The patients were randomized to receive 3 months of orlistat or no therapy (off), then crossed over to the other arm, and this sequence was then repeated. Fasting serum triglyceride levels, fat-soluble vitamins, and gastrointestinal side effects were assessed. RESULTS: Compared with the two off periods, orlistat therapy reduced serum triglycerides by 53.3% and 53.0% in patient 1 and 45.8% and 62.2% in patient 2. There was no deficiency of fat-soluble vitamin levels, and their growth continued. There were no serious adverse effects of orlistat; patient 1 had a mild increase in passage of gas and bloating, and patient 2 had constipation with mild stool leakage. CONCLUSION: Orlistat is safe and highly efficacious in lowering serum triglycerides in children with T1HLP and should be the first-line therapy in conjunction with an extremely low-fat diet.